Evaluativity of Somatic Phraseology in Old English Versions of the Psalms - Mukhin, Sergey (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2025)
The research based on the Old English linguistic evidence of eight Anglo-Saxon Psalters dating from the 8th to 12th centuries focuses on the phenomenon of evaluativity proper to idiomatic word combinations with somatic components. The research sets the task of determining the inventory of substantive lexemes with corporeal anthropomorphic semantics in the text of the psalms. Subsequently, the frequency indicators of lexical somatisms and their phraseological productivity are subject to scrutiny to single out the high frequency somatic lexemes. Proceeding from the assumption that high frequency lexical somatisms tend to feature higher phraseological productivity, the research comes to concentrate on the ten frequently used substantive somatisms, and further attention is paid to the word combinations constituted by these somatisms. In compliance with the linguacultural approach it is presumed that the word-combinations thus formed can mostly be identified as idioms with a transferred phraseological meaning. It is noted that all Old English somatic idioms in the psalms are phraseological calques from Latin. On the example of the idiomatic word combinations with the components swiðre (right hand), heafod (head) and tunʒe (tongue) it is established that evaluativity of somatic idioms can fall into three types in conformity with the axiological potential of their key somatic components: positive, negative and binary. The study may be of interest to linguists specializing in phraseology, linguaculturology, and the history of English.